ANALYSIS OF CHANGING DYNAMICS OF THE POVERTY LEVEL IN KHORAZM REGION (Marketing Journal, 2026)
This article analyzes the dynamics of change in poverty rates in the Khorezm region.nnotation: this article analyzes the dynamics of change in poverty rates in the Khorezm region. It treated factors such as economic growth, social protection programs, educ ational attainment, labor market opportunities, agriculture, migrati.
Keywords: poverty; economic growth; social protection; level of education; opportunities in the labor market; Agriculture; migration; health; investments; Natural Resources